Effect of an orthosis on foot center of pressure translation for treatment of hallux valgus in patients with rheumatoid arthritis: A report of 17 cases - Takeshi Mochizuki; Koichiro Yano; Katsunori Ikari; Ken Okazaki (Elsevier, 2020)
Objectives: We aimed to investigate the change in the center of pressure (COP) path and distribution with or without orthosis for hallux valgus (HV) in patients with rheumatoid arthritis (RA). Methods: In total, 17 patients and 21 feet were enrolled. We measured the COP path using the COP path measurement device (F-Scan II system). The HV angle (HVA); the anteroposterior COP path length, which was measured as a percentage of the foot length (%Long); transverse width of the COP path which was measured from the most medial to the most lateral point and expressed as a percentage of maximum foot width (%Trans); and the final site of the walking locus were analyzed by comparing patients with RA with and without orthosis. Results: Testing without and with the orthosis showed that the HVAs were 31.8° ± 9.3° and 25.2° ± 6.8° (p < 0.001), the %Long values were 61.1% ± 5.5% and 69.2% ± 5.9% (p < 0.001), and the %Trans values were 28.0% ± 9.1% and 30.1% ± 8.3% (p = 0.108). The final site of the walking locus for the 1st interphalangeal joint without and with orthosis were 8 feet (38.1%) and 15 feet (71.4%) (p = 0.020), respectively. Conclusions: The results indicated that the orthosis for HV improved the walking path and should be considered as a therapeutic option in nonpharmacological treatment of RA.